Survey of Study on Internal Waves Detection in Synthetic Aperture Radar Image - Chong Jin-song; Zhou Xiao-zhong (Leida xuebao, 2013)
In recent years, Internal Waves (IWs) detection in Synthetic Aperture Radar (SAR) image has received considerable attentions in the area of marine remote sensing and has already become one of the most important marine applications of SAR. Typical research results at home and abroad are reviewed. Three areas of researches are introduced and summarized, including parameter inversion method of IWs, the effect of different SAR parameter and wind field conditions on IWs imaging, the 2-dimentional SAR imaging simulation of IWs.